2021
DOI: 10.1080/10872981.2021.1876316
|View full text |Cite
|
Sign up to set email alerts
|

Environments, processes, and outcomes - using the LEPO framework to examine medical student learning preferences with traditional and electronic resources

Abstract: Changes in medical student learning preferences help drive innovation in teaching and require schools and commercial resources to quickly adapt. However, few studies have detailed the relationship of learner preferences to the environment and teaching modalities used in the pre-clerkship years, nor do they incorporate third-party resources. Our study attempts to analyze learner preferences by comparing the use of traditional and third-party resources. In 2017-18, a survey was distributed to medical students an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…We conducted a pilot focus group with 6 fourth-year medical students at our institution after which we made small revisions to the focus group script. We revised the script as we conducted focus groups concordant with grounded theory technique . We ensured data saturation by using probing questions, exploring alternative views and perspectives, and member checking during the focus groups.…”
Section: Methodsmentioning
confidence: 54%
See 2 more Smart Citations
“…We conducted a pilot focus group with 6 fourth-year medical students at our institution after which we made small revisions to the focus group script. We revised the script as we conducted focus groups concordant with grounded theory technique . We ensured data saturation by using probing questions, exploring alternative views and perspectives, and member checking during the focus groups.…”
Section: Methodsmentioning
confidence: 54%
“…4 A 2-institution quantitative study comparing student preferences for medical school vs third-party resources found participants preferred third-party lecture length, teacher effectiveness, and material quality. 5 There is a notable research gap concerning students' decision-making processes about when and how to use third-party resources within the context of their school curriculum. If medical educators better understand the students' approach to learning, they may uncover novel opportunities to improve preclerkship education.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The "Learning Environment, Learning Processes, and Learning Outcomes" (LEPO) framework is another one BJJ curriculum designers might find useful. As a process of employing teaching as an activity, LEPO reworks learning and suggests that most learning happens outside structured lectures (Wong et al, 2021;Phillips et al, 2019). This curriculum framework supports active learning concepts and methodologies because it fundamentally operates under the same presupposition: learning occurs outside of lectures.…”
Section: Curriculum Frameworkmentioning
confidence: 88%
“…Online resources are likely to become an increasingly indispensable part of medical education, both formally through publishers and institutions, and informally through open‐access medical information sources [22]. FOAMed resources provide easily accessible, specific, and usually free information where textbooks and other conventional resources may not [23]. The COVID‐19 pandemic has further highlighted that students may turn to online sources when they represent the most convenient and accessible option [2].…”
Section: Discussionmentioning
confidence: 99%